DIMENSI PSIKIS MANUSIA: A-NAFS, AL’AQL, AR-RUH, AL-FITRAH, AS-SHODR, ALQOLBU, AL-FUAD - Zilvi Syalsabillah; Nadirah Syafitri; Mikail Aydin; Khoirul Aziz; Muhammad Takrip (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This study aims to examine the psychological dimensions of human beings from the perspective of the Qur’an using a thematic interpretation (maudhu‘i) approach. In Islamic perspective, humans consist not only of physical elements but also psychological and spiritual dimensions that influence personality and behavior. These dimensions include an-nafs, al-‘aql, ar-ruh, al-fitrah, as-shadr, al-qalb, and al-fu’ād, which have different yet complementary roles. This research uses a library research method with a descriptive analytical approach. Data were collected from relevant books and journals and analyzed through thematic interpretation by gathering Qur’anic verses related to human psychological dimensions. The findings show that these dimensions are dynamic and interconnected, where an-nafs functions as the source of impulses, al-‘aql as reasoning, ar-ruh as the spiritual element, and al-fitrah as the basic potential toward goodness, while as-shadr, al-qalb, and al-fu’ād function as centers of emotional and spiritual awareness.